The ordinary parent's guide to teaching reading - Wise, Jessie (Peace Hill Press, 2005)
A guide to teaching phonics that explains how every parent can teach reading, includes a scripted format that guides parents and children through each lesson, from beginning vowel sounds through words on a fourth-grade level.